Prospects for the application of the mechanism of municipal-private partnership (MPP) - S. A. Kirzhinova; M. S. Nakhusheva (Новые технологии)
The article is devoted to the problematic issues of the implementation of municipal-private partnership practices and the prospects for its development. The author of the article proposes a revision of those areas where MPP can be successfully implemented, and the expansion of their spectrum. It is noted that the area which is undeservedly ignored by local authorities in the context of attracting private partners is cultural and leisure services. The sphere of tourism is also highlighted as promising in this context. The problem of a high level of bureaucracy and the cumbersome procedures of municipal-private partnerships has been identified; it was determined that the problem of lack of awareness and qualification of private partners remains relevant. According to the authors, formation of a training system, creation of educational programs, hotlines and information centers, communication channels for communication with representatives of the commercial sector are promising. The authors of the article have come to the conclusion that it is necessary to reform the system of financial regulation of PPP mechanisms by intensifying the practice of investing in infrastructure bonds and expanding the list of special economic zones. The problem of regional inequality in relation to the ongoing PPP projects has been highlighted, which requires a restructuring of approaches to the territorial diffusion of PPP projects. A problematic aspect of PIL is, among others, the lack of separate tools and practices for monitoring the effectiveness of partnerships. The prospects of joint efforts of municipalities and private business in the field of achieving sustainable development goals and implementing joint projects in the areas of waste processing, water treatment, etc. have been proposed.